2020
DOI: 10.34067/kid.0004722020
|View full text |Cite
|
Sign up to set email alerts
|

A Model To Estimate Glucose Absorption in Peritoneal Dialysis: A Pilot Study

Abstract: Background: Glucose absorption in peritoneal dialysis (PD) patients may contribute to adverse metabolic effects. Previous studies on glucose absorption were done on continuous ambulatory PD (CAPD) patients, with long dwell time. However, the growing majority of contemporary PD patients perform automated peritoneal dialysis with short dwell time. Moreover, membrane characteristics and dwell time determine small solute transport across the peritoneal membrane. Methods: In our pilot study, we used data from perit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…PD not only drains ascites but also prevents its accumulation by increasing ascites static pressure 17 . Furthermore, dialysate may serve as a calorie source, which is beneficial for cirrhotic patients experiencing malnutrition and appetite loss 18 . Clinical trials have shown that concerns regarding albumin loss and a high incidence of infectious peritonitis did not materialize 19 .…”
Section: Mechanism Of Pdmentioning
confidence: 99%
“…PD not only drains ascites but also prevents its accumulation by increasing ascites static pressure 17 . Furthermore, dialysate may serve as a calorie source, which is beneficial for cirrhotic patients experiencing malnutrition and appetite loss 18 . Clinical trials have shown that concerns regarding albumin loss and a high incidence of infectious peritonitis did not materialize 19 .…”
Section: Mechanism Of Pdmentioning
confidence: 99%
“…Additionally, PD may serve as a much needed source of calories in malnourished KF patients with ascites (Box 1). 36 Therefore, PD should be considered a viable and perhaps the preferred dialysis option in KF patients with ascites.…”
Section: Kidney Replacement Therapy In Patients With Kf and Ascitesmentioning
confidence: 99%